2019
DOI: 10.3847/1538-4357/aaff64
|View full text |Cite
|
Sign up to set email alerts
|

The First Galaxy Cluster Discovered by the VISTA Variables in the Vía Láctea Survey

Abstract: We report the first confirmed detection of the galaxy cluster VVV-J144321-611754 at very low latitudes (l = 315.836 • , b = -1.650 • ) located in the tile d015 of the VISTA Variables in the Vía Láctea (VVV) survey. We defined the region of 30× 30 arcmin 2 centered in the brightest galaxy finding 25 galaxies. For these objects, extinction-corrected median colors of (H -K s ) = 0.34 ± 0.05 mag, (J -H) = 0.57 ± 0.08 mag and (J -K s ) = 0.87 ± 0.06 mag, and R 1/2 = 1.59 ± 0.16 arcsec; C = 3.01 ± 0.08; and Sersic i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 39 publications
(43 reference statements)
3
11
0
Order By: Relevance
“…These are small objects with distributions that have peaks with 𝑅 1/2 ∼ 1.3 arcsec, 𝐶 with 3 https://catalogs.oac.uncor.edu/vvv_nirgc/ a value of approximately 3, and 𝑛 around 4. These results are similar to those found in the tiles analysed in Baravalle et al (2018Baravalle et al ( , 2019, which are characteristic of early-type galaxies. The galaxies with WISE data are brighter and with slightly larger sizes with a smaller Sérsic index than the galaxies, in general, in the VVV NIRGC.…”
Section: The Vvv Nir Galaxy Cataloguesupporting
confidence: 89%
See 3 more Smart Citations
“…These are small objects with distributions that have peaks with 𝑅 1/2 ∼ 1.3 arcsec, 𝐶 with 3 https://catalogs.oac.uncor.edu/vvv_nirgc/ a value of approximately 3, and 𝑛 around 4. These results are similar to those found in the tiles analysed in Baravalle et al (2018Baravalle et al ( , 2019, which are characteristic of early-type galaxies. The galaxies with WISE data are brighter and with slightly larger sizes with a smaller Sérsic index than the galaxies, in general, in the VVV NIRGC.…”
Section: The Vvv Nir Galaxy Cataloguesupporting
confidence: 89%
“…The galaxy cluster VVV-J144321-611754, identified in Baravalle et al (2019), is located in a less dense region (the d015 tile, 𝑙 = 315.8 • and 𝑏 = -1.6 • ). As it is very important to know which of these observed over-densities of galaxies are real structures, addi-tional observations, i.e.…”
Section: Parametermentioning
confidence: 99%
See 2 more Smart Citations
“…These latter authors detected and characterised the candidates using a combination of SExtractor and PSFEx techniques. Recently, Baravalle et al (2019) confirmed the existence of these galaxy candidates with spectroscopic data using Flamingos-2 at GEMINI Observatory. All these works confirm the potential of the VVV for detecting new extragalactic objects.…”
Section: Introductionmentioning
confidence: 80%